Algorithm for computing the propagator for higher derivative gravity theories - Accioly, A. [UNESP]; Ragusa, S.; Mukai, H.; De Rey Neto, E. [UNESP] (Springer Nature, 2000)
A simple algorithm for computing the propagator for higher derivative gravity theories based on the Barnes-Rivers operators is presented. The prescription is used, among other things, to obtain the propagator for quadratic gravity in an unconventional gauge. We also find the propagator for both gravity and quadratic gravity in an interesting gauge recently baptized the Einstein gauge [Hitzer and Dehnen, Int. J. Theor. Phys. 36 (1997), 559].